Tourism Stocks in Times of Crises: An Econometric Investigation of Non-macro Factors - Anastasios Zopiatis; Christos S. Savva; Neophytos Lambertides; Michael McAleer (Tinbergen Institute, 2016)
Following the recent terrorist attacks in Paris, the European media emphatically pronounced that billions of euros were wiped from tourism related stocks. This comes at a troublesome time for the tourism industry, in the midst of a global financial crisis, and the unpredictable rise of radical Islamic ideologies, which have caused chaos in the Middle East and Europe. The relationship and vulnerability of the industry to non-macro incidents have been well documented in the literature, mostly in theoretical terms. Nevertheless, the quantifiable impact of such events on tourism-specific stock values, both in terms of returns and volatility, received much less attention. With the use of an econometric methodology, the paper aims to enhance our conceptual capital pertaining to the effects of such possibilities on five hospitality and tourism stock indices. The empirical findings are of interest to stakeholders at all echelons of the spectra of the tourism and financial industries.
Keywords: C21; C58; G01; H12; Z32; 330; Tourism; Terrorism; Stock Market; Event Study; GJR; Econometric Modeling